First look at an easier example:
f(x) = 3x^2
f'(x) = 6x
pi is a constant, so:
f(x) = pi*x^e
f'(x) = e*pi*x^(e-1)
You can check the answer by integrating.
G
2007-01-10 17:26:20
·
answer #1
·
answered by disgruntledpostal 3
·
1⤊
0⤋
f(x) = [(pi)(x)]^e
The first thing we need to do is bring each of those inside terms to the power of e. After all, (ab)^n = a^n b^n
f(x) = (pi^e)(x^e)
Note that pi to the power of e is simply a constant. For that reason, when we take the derivative, we ignore it and take the derivative of the rest.
f'(x) = (pi^e) (ex^(e - 1))
Cleaning this up a bit,
f'(x) = e * pi^e * x^(e - 1)
2007-01-10 17:00:57
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
(e(pi^2)x)^(e-1)
We would use the chain rule in this circumstance. u=(pi)x
u^e=eu^(e-1). Substitute u and multiply by du/dx.
(pi)x^e=(e(pi^2)x)^(e-1)
I hope that this helps.
2007-01-10 16:57:52
·
answer #3
·
answered by unhrdof 3
·
0⤊
0⤋
y=(pi x)^e
y'=e(pi x)^(e-1) * pi
by general power rule
2007-01-10 16:59:12
·
answer #4
·
answered by Professor Maddie 4
·
0⤊
0⤋
Differentiate (Ïx)^e with respect to x. Ï and e are just contants so:
(Ïx)^e = (Ï^e)(x^e)
d{(Ï^e)(x^e)}/dx = e(Ï^e)x^(e-1)
2007-01-10 18:35:45
·
answer #5
·
answered by Northstar 7
·
0⤊
0⤋
d/dx[pi*x]^e = (pi^e)d/dx[x^e]
d/dx[x^e] = e*x^(e-1)
so d/dx[pi*x]^e = (pi^e)(e)x^(e-1)
2007-01-10 16:57:40
·
answer #6
·
answered by kellenraid 6
·
0⤊
0⤋
y=(лx)^e
y'=e*л^e * x^(e-1)
2007-01-10 16:59:16
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋
y = (лx)^e = (Ï^e)(x^e)
y' = e(Ï^e)x^(e - 1) = (e(лx)^e)/x
2007-01-10 17:04:34
·
answer #8
·
answered by Helmut 7
·
0⤊
0⤋